Beyond the Classroom: Collaboration or Exploitation?. Issue 3 (1st October 2020) - Roy, Loriene
ABSTRACT: Contact with students often leads to successful collaborative work outside of the classroom. Some contact is not as collaborative and may result in faculty learning how to protect their intellectual property and due recognition.